DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) SKILLS AMONG STUDENTS WITH LEARNING DISABILITIES (SLD) IN MALAYSIA AND UKRAINE - Rohaizat Ibrahim; Noraini Abdullah; Ciptro Handrianto; Irna Liza Muliana; Nataliia Nykonenko (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2021)
This study aims to develop Information and Communication Technology (ICT)’s skills for Students with Learning Disabilities (SLD) in Malaysia and Ukraine. Methodology used in this study is based on the Universal Learning Design implementation which involved three phases: Preparation, Integration and Assessment. The Preparation and Integration Phases are the stages for designing ICT activities and practicing digital skills. While the Assessment Phase is the phase to determine the usability of ICT for SLD. The findings of the study show that the Preparation and Integration Phases study are the most effective types of activities for digital skills development. It is obtained from the opinion of the experts in ICT related to learning content ranging from simple to complex with a defuzzification value of 0.939. The results of the Assessment Phase show that SLD can develop their ICT’s skills by using videos related to real situations. It also provides SLD with activities that can build a communication network between them and public and private institutions. All these activities were provided to stimulate and motivate them to work hard to achieve the desired goals.